Peran Media Massa Dalam Komunikasi Politik - Riris Silvia Tampubolon; Riris Silvia Br. Tampubolon; Azzahra Putri Hermaya; Herwin Herwin (Universitas Muhammadiyah Enrekang, 2022)
Mass media is a channel for delivering messages to a wide audience. In communication, mass media plays a very important role in the process of delivering information accurately and quickly. Mass media helps facilitate the process of delivering information and communication processes both in organizational and political forms. In the political context, the mass media is not only an integral part of politics, but is central to politics. This study aims to determine the role of mass media in political communication. In this study, the authors used descriptive qualitative research with data collection techniques obtained through literature and exploratory studies. So that the authors can draw the conclusion that in political communication, the mass media plays a role in conveying political campaigns, disseminating political information, and influencing the audience regarding politics